Interação das variáveis climáticas e ambientais na formação de microclimas em ambientes urbanos e rurais do Nordeste Paraense. - PFEIFF, Greicy Kelly (Universidade Federal do Pará, 2023)
Globalization has led to an increase in rural exodus over the past few decades. This process caused the crowding of people in large and small cities. These changes associated with land use triggered the appearance of microclimates in urban areas. In this context, the objective of the research was to evaluate the climatic and environmental conditions of the municipalities of Colares, São Caetano de Odivelas, Santo Antônio do Tauá, and Vigia that make up a mesoregion of the Northeast of Pará. Data on land use and land cover change from the MapBiomas project, AQUA / TERRA satellite images from the MODIS sensor, and from the Landsat 5 TM and 8 OLI / TIRS were used with the help of the Google Earth Engine platform to estimate the rates of vegetation, land surface temperature and surface heat islands between 1990 and 2020. Observed data on air temperature, relative humidity and were collected in the project “Understanding the regional climate variability in Northeast Paraense” from January to December 2010. The results showed an increase in population in the four municipalities from 1990 to 2020, which triggered the reduction of several factors such as the natural vegetation and quality of vegetation fragments. In addition, the population growth promoted the increase of surface temperature and surface heat island formation. The air temperature varied throughout the year, but the ability to present a heterogeneous behavior characterized by the rainy and less rainy period. The thermal comfort index was classified as partially comfortable in rural areas and uncomfortable in urban areas. It was possible to conclude that the urban microclimate has changed in the last 30 years. In addition, climate change can promote the intensification of these changes. Thus, the analysis of meteorological and environmental variables in an interdisciplinary way can assist in managing the landscape of the municipalities to mitigate the effects of heat islands and maintain the quality of life of the population.